Alginate-Based Delivery Systems for Bevacizumab Local Therapy: In Vitro Structural Features and Release Properties - Ferreira, Natália Noronha [UNESP]; Caetano, Bruno Leonardo [UNESP]; Boni, Fernanda Isadora [UNESP]; Sousa, Flávia; Magnani, Marina [UNESP]; Sarmento, Bruno; Ferreira Cury, Beatriz Stringhetti [UNESP]; Daflon Gremião, Maria Palmira [UNESP] (Elsevier, 2019)
Alginate-based polyelectrolyte complexes (PECs) and hydrogel were engineered as platforms for local bevacizumab (BVZ) therapy. This study provides deep comprehension on the microstructures of such systems, and their correlation with drug-release patterns. PECs and hydrogel were characterized using Fourier transform infrared spectroscopy, small-angle X-ray scattering, scanning electron microscopy, atomic force microscopy, and porosimetry. Structural investigations indicated that PECs are formed by supramolecular interactions, resulting in physically cross-linked polymer networks, whereas the BVZ-loaded hydrogel has a more compact and rigid structure, promoting better entrapment of BVZ. PECs and hydrogel were able to control the BVZ release for 4 and 8 days, respectively. Their release profiles correlated best with the Higuchi and Korsmeyer-Peppas models, respectively, indicating drug diffusion as the limiting step for drug release. Furthermore, BVZ remained biologically active in vitro after its incorporation into the hydrogel system. Together, these studies confirm that PECs and hydrogel exhibit different porous structures and physicochemical properties, making them promising platforms that allow the modulation of BVZ release meeting different requirements.
Keywords: alginate hydrogel; bevacizumab-alginate polyelectrolyte complexes; supramolecular interactions; sustained release; system microstructure